PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT (TGT) TERHADAP MUTU HASIL BELAJAR SISWA DI SMKN 1 PURWAKARTA - Irna Wahyuningsih, - (2021)
Team game tournament learning method is a type of cooperative learning that placing students in study groups that each groups have different members (ability, gender, ethnicity or race). This research was conducted at SMKN 1 Purwakarta. Sample on This research is the XI students of Electrical Power Installation Engineering 36 people. As for The purpose of this study is to determine the quality of student learning outcomes before and after the implementation of the team game learning method tournament on the subject of electric lighting installations. Research design used is pre-experimental with the type of one group pretest and posttest design. The results of this study, showed changes in increasing in the cognitive domain from the pre-test results obtained an average value of 40. Meanwhile, from the post-test results obtained an average value of 80.75. On affective domain of the three meetings conducted, at the first meeting obtained an average result of 80, at the second meeting with an average value of 86.56 and at the third meeting an average value of 90.94. On the realm psychomotor obtained an average value of 85.97. Based on those results it can be seen that the quality of student learning outcomes in the cognitive, affective, and psychomotor increase.